2013
DOI: 10.1002/adma201302015
|View full text |Cite
|
Sign up to set email alerts
|

25th Anniversary Article: Reversible and Adaptive Functional Supramolecular Materials: “Noncovalent Interaction” Matters

Abstract: Supramolecular materials held together by noncovalent interactions, such as hydrogen bonding, host-guest interactions, and electrostatic interactions, have great potential in material science. The unique reversibility and adaptivity of noncovalent intreractions have brought about fascinating new functions that are not available by their covalent counterparts and have greatly enriched the realm of functional materials. This review article aims to highlight the very recent and important progresses in the area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
224
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(318 citation statements)
references
References 134 publications
1
224
0
1
Order By: Relevance
“…[1][2][3] Research has focused on the spatiotemporal behavior of molecular assembly and, especially, the dynamics of these materials when utilized in life systems 4,5 and soft devices. 6,7 Various experimental and theoretical studies on assembly behavior have been reported and reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Research has focused on the spatiotemporal behavior of molecular assembly and, especially, the dynamics of these materials when utilized in life systems 4,5 and soft devices. 6,7 Various experimental and theoretical studies on assembly behavior have been reported and reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…[223,224] Extensive work has been done to demonstrate self-healing dielectric material [225] and gels, [226,227] however it is challenging to fabricate a self-healing current collector for the realization of a completely self-healing transparent and stretchable electronic device. It is extremely difficult to achieve selfhealing ability with electronic conductors.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Meanwhile, the ionic conductor can be easily tuned to repair itself while sustaining its transparency, stretchability, and ionic conductivity. One way to realize a self-healing ionic conductor is by using a polymer matrix comprised of bonds that are stable and reversible such as dynamic covalent bonds [223,224] and hydrogen bonds. [231,232] Cao et al reported highly self-healing STIC using ion-dipole interactions.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Owing to the dynamic nature of the noncovalent interactions, supramolecular polymers exhibit unique properties such as reversibility, stimuli‐responsiveness, self‐healing, and good processability 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. Over the past decades, significant advances have been made in developing methods of supramolecular polymerization, from spontaneous to controllable and living supramolecular polymerization 31, 32, 33, 34, 35, 36, 37, 38.…”
mentioning
confidence: 99%